2018
DOI: 10.3892/ol.2018.8183
|View full text |Cite
|
Sign up to set email alerts
|

Betulin induces cytochrome c release and apoptosis in colon cancer cells via NOXA

Abstract: Betulin is a common triterpene that can be readily obtained from various plants, particularly birch trees, in their natural environment. Specific tumor cells are sensitive to betulin, whereas healthy cells are not. Betulin was observed to stimulate programmed cell death of various cancer cell lines; however, the precise molecular mechanism of action of betulin remains unknown. The present study used colon cancer cells, in which mass apoptosis triggered by betulin was identified, and the apoptotic process was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Zhou et al. proved also that betulin is able to stimulate programmed cell death in colon cancer cells, demonstrating that the overexpression of NOXA enhanced betulin‐induced apoptosis [66] . Additionally, Wick et al.…”
Section: Discussionmentioning
confidence: 95%
“…Zhou et al. proved also that betulin is able to stimulate programmed cell death in colon cancer cells, demonstrating that the overexpression of NOXA enhanced betulin‐induced apoptosis [66] . Additionally, Wick et al.…”
Section: Discussionmentioning
confidence: 95%
“…Although betulin induces cell cycle arrest and autophagy, it has a meagre effect compared to reduction of CRC cell viability. Several studies have reported that betulin shows selective inhibitory effects on proliferation of several cancer cells by inducing caspase-3-and caspase-9-mediated apoptosis [31][32][33]. In addition, betulin can regulate expressions of Bcl-2 and Bax in gastric and cervical cancer cells [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Cytc, the hemoprotein located in cell mitochondria, plays role in mitochondrial electron transport, cardiolipin peroxidation (Kagan et al, 2005), ROS formation, and cell apoptosis (Cai et al, 1998). Regarding cell apoptosis, several compounds such as tamoxifen (an anticancer drug for breast cancer) and botulin (triterpene from plants, e.g., birch trees) induce the release of Cytc from mitochondria in a dose-dependent manner (Hassan et al, 2018;Zhou et al, 2018). BAG3, the protein belonged to the member of BAG family, plays a role in the protection of cells from the apoptosis process by stabilizing antiapoptotic Bcl-2 family proteins as bcl-2 and bcl-XL (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%